Emergence of metallic surface states and negative differential conductance in thin β-FeSi2 films on Si(001). (5th April 2023) - Sagisaka, Keisuke; Kusawake, Tomoko; Bowler, David; Ohno, Shinya
Abstract: The electronic properties of the surface of β -FeSi2 have been debated for a long. We studied the surface states of β -FeSi2 films grown on Si(001) substrates using scanning tunnelling microscopy (STM) and spectroscopy (STS), with the aid of density functional theory calculations. STM simulations using the surface model proposed by Romanyuk et al (2014 Phys. Rev. B 90 155305) reproduce the detailed features of experimental STM images. The result of STS showed metallic surface states in accordance with theoretical predictions. The Fermi level was pinned by a surface state that appeared in the bulk band gap of the β -FeSi2 film, irrespective of the polarity of the substrate. We also observed negative differential conductance at ∼0.45 eV above the Fermi level in STS measurements performed at 4.5 K, reflecting the presence of an energy gap in the unoccupied surface states of β -FeSi2 .